Haemarthrosis model in mice: BSS – Bleeding Severity Score assessment system. (25th July 2016) - Hakobyan, N.; Valentino, L. A.; Cong, L.; Enockson, C.; Song, X. Q.; Desai, S.; Radtke, R.; Fogg, L. F.
Abstract : Introduction: The prophylactic administration of clotting factor concentrate is currently the most effective strategy for the prevention of joint bleeding. As new agents with different mechanisms of action and administration schedules are developed, it will be important to study them in relevant preclinical models. Aim: The aim of this study was the standardization of a mouse haemarthrosis model in a haemophilia mouse and the development and validation of a comprehensive bleeding assessment system, the Bleeding Severity Score (BSS). Methods and Results: Four outcome measurements were assessed, two of which, the extra‐articular bleeding score and intra‐articular bleeding score, were determined to be the most reliable and were summarized into a BSS which was validated using a mouse haemarthrosis variability model. Conclusion: Using this model, the haemostatic effect of prospective drugs can be assessed in a clinically relevant joint bleeding model and will significantly increase the value of preclinical studies.